Concepções sobre o processo de ensino - aprendizagem em geometria no 8º ano fundamental em uma escola de Manaus - Rodrigues, Jorge de Menezes (2013)
This study aimed to analyze the teaching - learning process in the classes of geometry from its relation with daily life of the students. We seek to understand through the teaching practices of two math teachers how to establish the relation between the concept of geometry and daily life of the student. The research was conducted from a qualitative approach based on Bogdan and Biklen (1994), Creswell (2007), Flick (2009), Gil (2010) and Triviños (1987). For discussion related to the history of geometry the study was supported in Boyer (1996), Eves (2004), Pereira (2005) and Oliveira (2004). When considering ethnomathematics, we have dialogued with the following theoretical: Adam (2004), D'Ambrosio (2007), Knijnik and Duarte (2010), Passos, Caroline (2008). In the approach to teaching everyday concepts in geometry the references were Ávila (2010), Cenci and Costa (2011), Rego (2008), Vygotsky (1997) and the NCP (1998). Our study was based on an action research, and the data were collected in two classes of the 8th year of elementary school in a public school in the city of Manaus. Students enrolled in the two classes and two 8th grade math teachers have participated in this study according to the inclusion and exclusion criteria established by the researcher. The instruments and the research technique used for data collection were initial and final questionnaires, interviews and participant observations conducted during class. As a result of the research, the analysis of the data showed the importance of a work directed to the teaching of geometry to establish connections between geometric concepts and daily life of the student from a particular sociocultural context, because this relationship provides an environment reflection and discussion among students and the teacher providing an understanding of geometric concepts.